Connectedness among crude oil prices, stock index and metal prices: An application of network approach in the USA. (August 2019) - Husain, Shaiara; Tiwari, Aviral Kumar; Sohag, Kazi; Shahbaz, Muhammad
Abstract: We investigate the connectedness among crude oil prices, stock index and metal prices covering the period of 1990M1-2017M3 for US economy applying time domain Spillover Index framework byDiebold and Yilmaz (2012) . We contribute to the literature by developing network-based approach generated from time domain spill-over methods. It is evident that the stock index is neither price spillover receiver nor contributor. Our investigation demonstrates that palladium, gold, platinum and silver are net contributors of volatility spillover whereas crude oil, titanium, steel, and silver are net receivers of volatility spillover. The identification of the net recipient and receiver of volatility spillover appears challenging measured by the magnitudes of net volatility spillovers index in the presence of economic crises including global financial crisis 2008–2009 and European Sovereign Debt Crisis period 2010–2012. Highlights: This study focuses on the spillover effect among crude oil prices, stock index and precious metal prices. Palladium, gold, platinum and silver are net contributors of volatility spillover. Crude oil, titanium, steel, and silver net receivers of volatility spillover. Volatility spillovers fluctuated in the presence of recent global financial crisis.